Hearing the Voices of HIV Positive Women in Kenya: Secondary Analysis of Interview Data Using Dialogic/Performance Analysis - (:unkn) unknown (My University, 2015)
The purpose of the study is to demonstrate the use of the dialogic/performance methodology in health research by conducting a secondary analysis of interview data collected from women in Kenya who are HIV positive. Dialogic/performance analysis is a dynamic, interpretive narrative analytical technique. Qualitative research literature inadequately provides specific methodological guidance especially when reusing a data set. Further, the use of the dialogic/ performance method is very limited in health research. These factors point to the significance of this work in explaining dialogic/ performance analysis thereby potentially expanding its use by both novice and experienced qualitative researchers. Guidance for conducting a qualitative health research study using dialogic/performance analysis is provided through a critical review of selected studies and an explanation of how this method was applied to the interviews of these women. Skeptics of qualitative secondary analysis question whether methodological challenges can be overcome sufficiently to produce research studies that are trustworthy, sound and meaningful. A secondary intent of this research is to illustrate how methodological issues/concerns related to conducting a qualitative secondary analysis are addressed in the context of using dialogic/performance analysis of narrative data. A discussion of challenges such as context, researcher presence, suitability of data set and other concerns are addressed through a discussion of how these concerns were resolved in this analysis of the interviews. Finally, the actual findings from conducting this analysis are presented. The analysis shifts the perspective from an exploration of what the researcher wants to know to giving opportunity to hear the voices of these HIV positive women as they tell their stories of the impact of an HIV-positive diagnosis on their identity and lives.
Keywords: Dialogic/Performance Analysis; HIV Positive Women; Narrative Analysis; Qualitative Methodology; Qualitative Secondary Analysis; Secondary Analysis